Banggai Folktales as Reading Materials for Developing Students’ Critical Literacy: A Qualitative Content Analysis - Anitha Thalib Mbau; Nurul Pratiwi; Nurafni Azzahra Dg Pacidda; Mifta Zalianti; Kasih Marchela Z. Larau (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Folktale has considerable potential as English reading material, not only for fostering students’ cultural awareness but also for developing their critical literacy. In the current digital era, students are exposed to massive amounts of information that cannot be fully controlled, making critical literacy an essential skill. A critical lens enables students to analyze texts and information thoughtfully before forming judgments or taking action. This study, then, intended to analyze the potential Banggai folktales as English reading materials for developing students’ critical literacy. It applied a qualitative content analysis. The source of the data was Banggai folktales texts written in English. The researchers play vital roles as the main instrument for collecting and analyzing the data. The four dimensions of critical literacy—disrupting the commonplace, interrogating multiple viewpoints, focusing on sociopolitical issues, and taking action and promoting social justice— were used as the analytical framework. Peer debriefing was conducted to maintain the trustworthiness of the study. The results indicate that three Banggai folktales can effectively engage students across all four dimensions of critical literacy. To sum up, Banggai folktales have strong potential as alternative English reading materials to develop students’ critical literacy and encourage them to critically engage with complex and problematic social issues.